Directors and the New Musical Drama - Lundskaer-Nielsen, M. author. aut Link
X, 231 p.
Keywords: This is one of the first books to offer a rigorous analysis of the enormous changes in the musical theatre during the 1980s and 90s. In addition, it focuses on the contribution of well-known, serious theatre directors to the mainstream Musical Theatre and it is the first book to offer a dual Anglo-American perspective on this subject.